A Novel Laser Angle Selection System for Computed Tomography-Guided Percutaneous Transthoracic Needle Biopsies. Issue 2 (May 2023) - Xu, Huiting; Zhao, Yanjun; Yuan, Jiaqi; Li, Wei; Ni, Jianming
Purpose: To evaluate a novel laser angle selection system (LASS) for improving the efficiency of a computed tomography (CT)–guided percutaneous transthoracic needle biopsy (PTNB).Methods: Thirty-eight patients referred for CT-guided PTNB were randomly separated into a LASS-assisted puncture group (18 patients) or conventional freehand control group (20 patients). The puncture time, number of control CT scans, and patients' radiation dose were compared for each group.Results: The lesion size, target-to-pleural distance, planned puncture depth, and angle of the two groups were not significantly different. LASS-assisted PTNB significantly reduced the number of control scans (1.7 ± 0.8 vs 3.5 ± 1.5, P < .001) and the mean operation time (12.0 ± 4.3 min vs 28.8 ± 13.3 min, P < .001) compared with the conventional method. The corresponding room time (27.1 ± 6.6 min vs 44.1 ± 14.4 min, P < .001) and total radiation dose (7.9 ± 1.0 mSv vs 10.1 ± 1.7 mSv, P < .001) of each procedure also decreased significantly. Fifty-six percent (10/18) of the operations hit the target on the first needle pass when using LASS compared with 10% (2/20) using the conventional method.Conclusions: Compared with a conventional method, this novel laser angle simulator improves puncture efficiency with fewer needle readjustments and reduces patient radiation dose.